Angiogenic biomarkers in children with congenital heart disease: possible implications - Mohamed Nagwa A; El-Melegy Nagla T (BMC, 2010)
Abstract Background Vascular endothelial growth factor (VEGF), platelet derived endothelial cell growth factor/thymidine phosphorylase (PD-ECGF/TP) and leptin are known as potent angiogenic factors The objective of the study was to evaluate these angiogenic factors VEGF, PD-ECGF/TP and leptin in children with congenital heart disease (CHD) and the factors that lead to angiogenesis in such cases. Methods Sixty CHD children were studied and divided into two groups (n = 30); cyanotic-CHD (C-CHD) and acyanotic-CHD (A-CHD). Twenty five healthy children were included as controls. Results Significantly higher serum levels of VEGF, PD-ECGF/TP activity and leptin were detected in patients with CHD, particularly in patients with C-CHD. CHD patients with SpO2 <90%, pulmonary hypertension (PH), severe pulmonary stenosis (PS), detectable collaterals, cardiomegaly and/or heart failure showed significantly higher levels of these factors than those with higher SpO2 or those without these findings. Conclusion Hypoxia, PH and PS are important factors that lead to harmful angiogenesis. However, angiogenesis could be essential in some cases of CHD as coarctation of aorta to enhance renal perfusion. This may provide new ways for therapeutic strategies aiming at reducing or promoting angiogenesis in CHD to improve patient's outcome.